Incomplete lineage sorting and hybridization in the evolutionary history of closely related, endemic yellow-flowered Aechmea species of subgenus Ortgiesia (Bromeliaceae) - Goetze, Marcia; Zanella, Camila M.; Palma-Silva, Clarisse [UNESP]; Buttow, Miriam V.; Bered, Fernanda (Botanical Soc Amer Inc, 2017)
PREMISE OF THE STUDY: The yellow-flowered Aechmea subgenus Ortgiesia (yfAsO) (Bromeliaceae) is a group of seven morphologically similar bromeliads found mostly in the southern Brazilian Atlantic rainforest. The recent origin of this group probably contributes to its taxonomic complexity. The aims of this study were to investigate the levels of genetic diversity and structure at the population and species levels, to gain insight into the processes behind the diversifi cation of the group, and to contribute to the establishment of species boundaries. METHODS: We sequenced two noncoding regions of the chloroplast genome (rpl32-trnL and rps16-trnK) and the nuclear phyC gene in 204 and 153 individuals, respectively, representing the seven species of the group. Phylogeographical and population genetics approaches were used. KEY RESULTS: Three of the seven yfAsO showed some degree of genetic differentiation among species. Divergence time for the group was dated to around 4 million years ago. Areas of conservation value were identified, and a scenario of multiple refugiain the southern Brazilian Atlantic rainforest during the Pleistocene climatic oscillations is suggested. CONCLUSIONS: We hypothesized that incomplete lineage sorting and localized hybridization events are responsible for the low levels of genetic differentiation and the taxonomic complexity observed among and within the seven yfAsO species. Further studies on Aechmea comata and Aechmea kertesziae will be necessary to clarify the boundary between these two species. Most of the populations sampled showed high genetic diversity and/or unique haplotypes; they should be prioritized for conservation purposes.
Keywords: Brazilian Atlantic rainforest; Bromeliaceae; diversification; evolutionary history; genetic diversity; genetic structure; multiple refugia; phylogeography; Pleistocene